A possible role of microRNAs as predictive markers for the recurrence of hepatocellular carcinoma after liver transplantation. (28th January 2016) - Liese, Juliane; Peveling‐Oberhag, Jan; Doering, Claudia; Schnitzbauer, Andreas A.; Herrmann, Eva; Zangos, Stephan; Hansmann, Martin L.; Moench, Christian; Welker, Martin W.; Zeuzem, Stefan; Bechstein, Wolf O.; Ulrich, Frank
Summary: With favourable 5‐year survival rates up to 75%, liver transplantation (LT) is the treatment of choice for hepatocellular carcinoma (HCC). Nonetheless, tumour recurrence after LT remains a challenge. The aim of this retrospective study was to develop a predictive score for tumour recurrence after LT by combining clinical parameters with HCC biomarkers (microRNA). A microRNA (miRNA) microarray analysis was used to compare miRNA expression patterns in tissue samples of 40 patients with and without HCC recurrence after LT. In a screening cohort ( n = 18), the miRNA analysis identified significant differences in the expression of 13 miRNAs in patients with tumour recurrence. Using the most significant miRNAs in this screening cohort, we could develop a predictive score, which combined the expression levels of miR‐214, miR‐3187 and the Milan criteria, and we could define low‐ and high‐risk groups for tumour recurrence and death. The above score was evaluated in a second and independent cohort ( n = 22). In contrast to the Milan criteria alone, this score was significantly associated with tumour recurrence. Our analysis indicated that the use of a specific miRNA expression pattern in combination with a limited tumour burden as defined by the Milan criteria may lead to a more accurate prediction of tumour recurrence.